2015
DOI: 10.14748/ssp.v2i2.1315
|View full text |Cite
|
Sign up to set email alerts
|

Research of interaction between metronidazole tablets and metal salts `in vitro`

Abstract: INTRODUCTION: Along with the efficacy and safety of drugs, the interaction of drugs with each other and with other accompanying substances is important, too. There are no data about the interaction or influence of antacids and other drugs with polyvalent cations on the metronidazole bioavailability. The purpose of this research was the studying of the metronidazole release kinetics from the tablets in an environment that simulates stomach conditions with the addition of metal salts, which are part of the wides… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…5 c shows the FTIR spectra of pristine MTZ and MTZ-B1-C1 hydrogel. From the figure, it is observed that the spectrum of pristine MTZ shows an absorption band at 3221 cm −1 (O–H stretching vibrations), band at and 3099 cm −1 (imidazole, C C–H, stretching vibration) [ 53 , 54 ], and the C–H of the methyl (–CH 3 ) groups and alkyl (–CH 2 –) chains stretching vibrational bands are at 2937 and 2853 cm −1 [ 55 ].…”
Section: Resultsmentioning
confidence: 99%
“…5 c shows the FTIR spectra of pristine MTZ and MTZ-B1-C1 hydrogel. From the figure, it is observed that the spectrum of pristine MTZ shows an absorption band at 3221 cm −1 (O–H stretching vibrations), band at and 3099 cm −1 (imidazole, C C–H, stretching vibration) [ 53 , 54 ], and the C–H of the methyl (–CH 3 ) groups and alkyl (–CH 2 –) chains stretching vibrational bands are at 2937 and 2853 cm −1 [ 55 ].…”
Section: Resultsmentioning
confidence: 99%
“…Figure 4(b) shows the FTIR spectra of pristine MTZ and MTZ-H2-G3 hydrogel. From Figure 4(b), it is observed that the spectrum of pristine MTZ shows an absorption band between 3221 attributed to stretching vibrations of the O-H groups, peak at 3099 cm −1 is due to the stretching vibration of imidazole (C=C-H) [52,53], the peaks at 2937 and 2853 cm −1 are attributed to the stretching of the C-H of the methyl (-CH3) and alkyl (-CH2-) groups [54]. The peaks at 1807 cm −1 and 1473 cm −1 are due to asymmetric N-O stretching and symmetric stretching of NO 2 bonds.…”
Section: Ftir Analysis Figures 4(a)mentioning
confidence: 99%